Liquidity and Stock Returns: An Empirical Study of the U.K. Equity Market - Wang, Nana (2009)
The relationship between liquidity and stock returns for U.S. market has been examined widely in recent decades. Using the U.K. data, this paper explores that there is a liquidity premium for illiquidity stocks from the angle of liquidity level. Two approaches are employed in explaining the cross-sectional stock returns: cross-sectional regression and liquidity-sorted portfolio analysis. Furthermore, the robustness of liquidity premium is tested through the subperiod analysis and January effect. The excess return for illiquid stocks is more dominant in the month of January relative to the remaining months.